Triggering HIV polyprotein processing by light using rapid photodegradation of a tight-binding protease inhibitor - Schimer, Jiří; Pávová, Marcela; Anders, Maria; Pachl, Petr; Šácha, Pavel; Cígler, Petr; Weber, Jan; Majer, Pavel; Řezáčová, Pavlína; Kräusslich, Hans-Georg; Müller, Barbara; Konvalinka, Jan (Nature communications, 2015)
HIV protease (PR) is required for proteolytic maturation in the late phase of HIV replication and represents a prime therapeutic target. The regulation and kinetics of viral polyprotein processing and maturation are currently not understood in detail. Here we design, synthesize, validate and apply a potent, photodegradable HIV PR inhibitor to achieve synchronized induction of proteolysis. The compound exhibits subnanomolar inhibition in vitro. Its photolabile moiety is released on light irradiation, reducing the inhibitory potential by 4 orders of magnitude. We determine the structure of the PR-inhibitor complex, analyze its photolytic products, and show that the enzymatic activity of inhibited PR can be fully restored on inhibitor photolysis. We also demonstrate that proteolysis of immature HIV particles produced in the presence of the inhibitor can be rapidly triggered by light enabling thus to analyze the timing, regulation and spatial requirements of viral processing in real time.
Keywords: Aminocoumarins; aminokumariny; Models, Molecular; Time Factors; Virus Replication; Carbamates; vazba proteinů; časové faktory; karbamáty; Valine; Humans; kinetika; HIV Protease Inhibitors; Kinetics; valin; Photolysis; Light; Proteolysis; vazebná místa; fotolýza; inhibitory HIV-proteasy; světlo; Protein Precursors; proteolýza; proteinové prekurzory; Binding Sites; HEK293 Cells; lidé; molekulární modely; HEK293 buňky; HIV-proteasa; HIV-1; replikace viru; HIV Protease; Protein Binding